Current Status and Future Perspectives of Androgen Receptor Inhibition Therapy for Prostate Cancer: A Comprehensive Review - Kim, Tae Jin (Biomolecules, 2021)
The androgen receptor (AR) is one of the main components in the development and progression of prostate cancer (PCa), and treatment strategies are mostly directed toward manipulation of the AR pathway. In the metastatic setting, androgen deprivation therapy (ADT) is the foundation of treatment in patients with hormone-sensitive prostate cancer (HSPC). However, treatment response is short-lived, and the majority of patients ultimately progress to castration-resistant prostate cancer (CRPC). Surmountable data from clinical trials have shown that the maintenance of AR signaling in the castration environment is accountable for disease progression. Study results indicate multiple factors and survival pathways involved in PCa. Based on these findings, the alternative molecular pathways involved in PCa progression can be manipulated to improve current regimens and develop novel treatment modalities in the management of CRPC. In this review, the interaction between AR signaling and other molecular pathways involved in tumor pathogenesis and its clinical implications in metastasis and advanced disease will be discussed, along with a thorough overview of current and ongoing novel treatments for AR signaling inhibition.